Effects of Blanching and Hot Air Drying Conditions on the Physicochemical and Technological Properties of Yellow Passion Fruit (Passiflora edulis Var. Flavicarpa) by‐Products. Issue 3 (16th June 2016) - Duarte, Y.; Chaux, A.; Lopez, N.; Largo, E.; Ramírez, C.; Nuñez, H.; Simpson, R.; Vega, O.
Abstract: Passion fruit peel constitutes 50% of the whole fruit; therefore, a method to transform it to an active ingredient would be useful. Hot air drying is the most common process applied to extend the shelf life by reducing water activity. However, the processing conditions must be carefully selected to retain bioactive compounds. The goal of this study was to investigate the effects of blanching, temperature and airflow rate during hot air drying on the physicochemical and technological properties of passion fruit peel. A 3 2 experimental design with replicates in the central point was used. Three temperatures (50–55–60°C) and three airflow rates (2.4–2.7–3.0 m/s) were used, and the drying curves were analyzed to estimate the effective diffusion ( Deff ) and drying time. The dried peels were milled and their physicochemical properties (total fiber content and total polyphenol content), and technological properties (water holding capacity, the swelling capacity and the oil holding capacity) were measured. The results showed that the shortest drying time (∼2.5 h) was obtained at 60°C and 2.7 m/s for both control and blanched fruits. The physicochemical and technological properties were not affected by the drying conditions, because the temperatures used were not high enough to be detrimental. In addition, Deff and the physicochemical and technological properties were not affected by blanching due to preserve the samples a slower freezing process (freezing rate <1 cm/h) was performed, which can produce severe damage at the cellular level facilitating water diffusion and therefore can be considered such as pretreatment. Practical Applications: Considering that Passion fruit waste constitutes 50% of the whole fruit and that has a high potential, primarily because it is rich in bioactive compounds, such as vitamins, minerals, polyphenolic compounds with a high antioxidant capacity and dietary fiber it is important study an adequate process to allow stabilize and store the passion fruit by‐products. Therefore, the passion fruit by‐product can be used as active ingredient in the formulation of different kind of foods, specially bakery and pastry products.